2020
DOI: 10.7717/peerj.8589
|View full text |Cite
|
Sign up to set email alerts
|

A high Mn(II)-tolerance strain, Bacillus thuringiensis HM7, isolated from manganese ore and its biosorption characteristics

Abstract: Microorganisms play a significant part in detoxifying and immobilizing excessive metals. The present research isolated a strain (HM7) with high Mn(II) tolerance from Mn(II)-contaminated soil samples. The 16S rDNA sequence analysis showed that HM7 had a 99% similarity to Bacillus thuringiensis, which can survive under a high concentration 4,000 mg/L of Mn(II), and the highest removal rate was up to 95.04% at the concentration of 400 mg/L. The highest Mn(II) removal rate was detected at the contact time 72 h, te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 74 publications
(80 reference statements)
2
8
0
1
Order By: Relevance
“…A similar phenomenon was observed by Huang et al (2020) when evaluating the biosorption capacity of Mn(II) in a concentration range of Mn(II) (0-10000 mg/L) by the B. thuringiensis HM7 strain. The results showed that the growth of HM7 within a concentration range (200 -800 mg/L) was greater than without Mn(II) (Huang, et al, 2020). The effect of Cr(VI) concentrations on the population density of Paenibacillus sp.…”
Section: Molecular Identification With 16s Rrna Genesupporting
confidence: 80%
See 1 more Smart Citation
“…A similar phenomenon was observed by Huang et al (2020) when evaluating the biosorption capacity of Mn(II) in a concentration range of Mn(II) (0-10000 mg/L) by the B. thuringiensis HM7 strain. The results showed that the growth of HM7 within a concentration range (200 -800 mg/L) was greater than without Mn(II) (Huang, et al, 2020). The effect of Cr(VI) concentrations on the population density of Paenibacillus sp.…”
Section: Molecular Identification With 16s Rrna Genesupporting
confidence: 80%
“…This phenomenon may be due to the bacteria adapting differently to conditions of the environment, depending on the tolerance mechanism that these use (Dhal, et al, 2013;Rath, et al, 2014;Rath, et al, 2019). A similar phenomenon was observed by Huang et al (2020) when evaluating the biosorption capacity of Mn(II) in a concentration range of Mn(II) (0-10000 mg/L) by the B. thuringiensis HM7 strain. The results showed that the growth of HM7 within a concentration range (200 -800 mg/L) was greater than without Mn(II) (Huang, et al, 2020).…”
Section: Molecular Identification With 16s Rrna Genesupporting
confidence: 59%
“…Other researches observed the low Mn 2+ adsorption rate in an acidic condition (pH < 5), caused by the large amounts of protons like H 3 O + and H + , which increased the difficulty in binding sites of Mn 2+ to cell walls. When pH increased the higher removal rate was reached, which could be connected with more negatively charged cells available, promoting a greater metal uptake [34]. Another reason of this observation is that under acidic conditions, the carboxyl groups responsible for the retention of metals are protonated and restrict entry of metallic ions, whereas at a higher pH, these groups are negatively charged, facilitating the binding of the metals ions [43,44].…”
Section: Removal Efficiencymentioning
confidence: 99%
“…MSB 5 isolated from Sanindipur mines was also viable at even a 1000 mM concentration of MnCl 2 [5]. Meanwhile, Bacillus thuringiensis HM7 isolated from Xiangtan Mn ore in China was able to grow at 31.78 mM [34].…”
Section: Determination Of Mic and Effects Of Mn On Cellular Protein Expressionmentioning
confidence: 99%
“…The removal and regulation of Mn by microorganisms is mediated by metal-specific regulators that regulate low or sufficient concentrations of Mn inside the cell. This system is well characterized in bacteria, especially Gram-positive bacteria such as Bacillus spp., due to the fact that many studies have reported Mn bioremediation by Bacillus [ 44 , 151 , 152 , 153 ], whereas the Mn homeostasis mechanisms have been studied extensively over the years ( Table 1 ). In B. subtilis, Mn concentration is regulated by MntR, an Mn-specific metallo-regulator related to the DtxR/IdeR family [ 181 ], which serves important roles in the sensing of metals such as iron (Fe) and Mn in several bacterial species [ 189 ].…”
Section: Bacillus Species and Heavy Metalsmentioning
confidence: 99%